Determinants of Food Choices and Selection of Healthier Food Products by Adults (20–40 Years Old) Residing in Delhi. (14th June 2022) - Mediratta, Srishti; Mathur, Pulkit
Abstract: Objectives: This study was aimed to assess the factors influencing food choices, food label reading habits, and understanding of nutrition information on food labels among adults. Methods: The study had a cross-sectional study design with a non-probability purposive sampling technique where adults who engaged in food purchase were selected from housing colonies from four geographical zones of the city. Key informants were contacted and thereafter snowball sampling was applied to collect data using a mixed-methods approach from 589 adults (20–40 years). Statistical analysis was performed with a level of significance P < 0.05. Results: The most influential factors affecting food choices were brand (30%), nutritive value (22%), and taste (20%). Food selection depended on whether the adult had a meal with friends or family. Most participants read food labels (79%) and noticed nutrition and health claims (76%) on packaged food items. Most participants (80%) between 20–30 years read food labels and were most influenced by the health claim 'lowers cholesterol' (χ2 = 44.5, P < 0.001) compared to 30–40 year olds. Participants belonging to the upper-middle-income group were less likely to value nutrition over taste as compared to the high-income group while choosing food products adjusting for age, marital status, and gender (OR = 0.57, CI:0.381–0.86). Around 77% of participants believed that they understood nutritional information, though most (74%) could not identify whether foods were rich or low in specific nutrients. Females were more likely to understand nutrition information as compared to men (OR = 1.52, CI: 1.01–2.31). Among all the nutrient profiling models shown, the majority found the color-coded 'traffic light scheme' format easiest to understand. Conclusions: A combination of drivers influences food selection by an adult. The public health policy needs to adopt a food systems approach that brings about change in the food environment. The availability of healthy yet tasty alternatives needs to be encouraged and foods high in fat, salt, and sugar need to be discouraged. The packaging regulations need to ensure that food labels communicate about healthfulness in a simple manner to enable consumers to make better food choices. Funding Sources: The first author (S.M.) received a Senior Research Fellowship from the University Grants Commission (India).